(untitled) (REMUNOM, 2024)
This article explores parental alienation, a complex psychosocial phenomenon with significant consequences for child development, especially in the school context. Parental alienation occurs when one parent manipulates the child’s perception against the other, creating an environment of conflict that negatively affects family relationships, emotional health and the child’s academic performance. The relevance of the topic lies in the profound impact of this phenomenon on children with global disabilities, who already face additional challenges in the learning process. The main objective of the research is to investigate the damage caused by parental alienation in the school environment and analyze how these effects compromise the educational and emotional development of children with global disabilities. The research also proposes effective intervention strategies aimed at preventing andmitigating the harmful effects of parental alienation in the school context. The methodology adopted includes a theoretical review of the literature and the analysis of practical cases, with the aim of offering recommendations that promote a more inclusive and healthy educational environment.